Father to Son The Mediation of Family Firm Succession Conflict - Berkel, Hans-Georg (Edition KWV,, 2007)
Family firm research has shown that the cooperative resolution of conflict between the incumbent entrepreneur and his successor is crucial for the survival of the family firm. Dispute resolution research suggests that a third party acting as mediator can provide valuable support to their efforts. Father to Son synthesizes insights from both lines of research to propose when, and how, mediation can contribute to the resolution of family firm succession conflicts. It offers a clear framework to guide family firm members, as well as their advisors, through the succession process.